Hardiness as a Predictor of Job Readiness in Final Year Students - Iri', Yanses Kala'; Setyorini, Theresia Dewi; Lekahena, Femmy (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Students generally undergo lecture activities to prepare themselves to enter the world of work. However, in reality there are still many college graduates who are not yet working. Personality hardiness is often associated with an individual's ability to deal with pressure, in this case faced by students, especially final year students, when entering the world of work. The aim of this research is to find out whether there is a relationship between hardiness and work readiness in final year students at University X in Yogyakarta. The proposed hypothesis is that there is a positive relationship between hardiness and work readiness. This research involved 78 final year students. Data was collected using two scales: work readiness scale and hardiness scale. The Pearson Product Moment correlation test was used to carry out the analysis of this research. The results show that the correlation coefficient of hardiness with work readiness for final year students at University X in Yogyakarta is 0.622, with sig. p = 0.000, and effective contribution of 38.69%. Additional analysis results: The challenge aspect was 5.52%, the control aspect was 19.66%, and the commitment aspect was 13.50%.Mahasiswa pada umumnya menjalani kegiatan perkuliahan untuk mempersiapkan dirinya dalam memasuki dunia kerja. Walau demikian, pada kenyataannya masih banyak dari lulusan perguruan tinggi yang belum bekerja. Kepribadian hardiness seringkali di kaitkan dengan kemampuan individu dalam menghadapi tekanan, dalam hal ini yang dihadapi oleh mahasiswa khususnya mahasiswa tingkat akhir dalam memasuki dunia kerja. Tujuan dari penelitian ini adalah untuk mengetahui apakah ada hubungan antara hardiness dan kesiapan kerja pada mahasiswa tingkat akhir di Universitas X di Yogyakarta. Hipotesis yang diusulkan bahwa ada hubungan positif antara hardiness dan kesiapan kerja. Penelitian ini melibatkan 78 mahasiswa tingkat akhir. Data dikumpulkan menggunakan dua skala: skala kesiapan kerja dan skala hardiness. Uji korelasi Pearson Product Moment digunakan untuk melakukan analisis penelitian ini. Hasilnya menunjukkan koefisien korelasi dari hardiness dengan kesiapan kerja pada mahasiswa tingkat akhir di Universitas X di Yogyakarta sebesar 0,622, dengan sig. p = 0,000, dan sumbangan efektif sebesar 38,69%. Hasil analisis tambahan Aspek tantangan adalah 5,52%, aspek kontrol adalah 19,66%, dan aspek komitmen adalah 13,50%.